High performance computing : third Latin American Conference, CARLA 2016, Mexico City, Mexico, August 29-September 2, 2016, Revised selected papers /: third Latin American Conference, CARLA 2016, Mexico City, Mexico, August 29-September 2, 2016, Revised selected papers. (2017) - Unknown
No abstract available